The Determinants of Pro-Environmental Behavior Among Accounting Students in Indonesia - Latifah, Lyna; Kusmuriyanto, Kusmuriyanto; Wiharto, E. S. P.; Efendy, A. F.; Abdillah, F. M. (Universitas Negeri Semarang, 2023)
The objective of the study is to examine the influence of environmental literacy, University Supports on pro-environmental behavior by identifying environmental attitudes. The main contribution of this research is to give a description for higher education to integrate and to provide support or stimulus for students to behave pro-environment. The samples of this study are 304 accounting students from several universities in Indonesia. Data are analyzed with descriptive statistics and hypothesis testing. The hypothesis testing of this study uses Partial least squares (PLS) path modeling. Result shows that University Supports affect the environmental literacy. Attitude also acts as a mediating variable between University Supports to pro environmental behavior. But instead the environmental literacy had no effect on environmental pro behavior. Likewise, attitude also has no role in mediating the relationship.